PENGELOLAAN DAERAH PAINAN DALAM PERSPEKTIF KEPARIWISATAAN DI KECAMATAN IV JURAI KABUPATEN PESISIR SELATAN - Pertiwi, Mutiara - (STKIP PGRI Sumbar, 2014)
This study aims to determine the management of tourism Painan in perspective. Theproblems studied in this research is the neighbor management infrastructure to support theincrease of tourism in the city in District IV Jurai Painan South Coastal District. This research isqualitative. Determination of the informant obtained the Snowball technique. To answer theformulated problem can be used secondary data and primary data. Primary data was collectedthrough observations, interviews discussions with the tourism department and the competent,sound recordings and photographs taken in the field. The research location is in the district of thesouthern coastal district IV Jurai Painan.The research concludes that the management of facilities and infrastructures that existin the area Painan still inadequate, funding limitations also affect the process of managing thefacilities and infrastructure. The work is not maximized, because the stage of development, and thelack of cooperation between government and local communities in the management of this Painanfor the development of tourism.In the development of tourism in the area Painan local governments have plans andsupervision is good enough, that will make a flyover of a hill Langkisau breaking through to thehill and up the hill to the taps. Work on it will be done soon because nowadays have started in thearea Painan known by outsiders and foreign. If the bridge is completed Painan area certainlymuch better than the present.